Modified SWCNTs with Amphoteric Redox and Solubilizing Properties1. Issue 24 (18th May 2014) - Rodríguez‐Pérez, Laura; García, Raúl; Herranz, María Ángeles; Martín, Nazario
Abstract A complementary double‐covalent functionalization of single‐wall carbon nanotubes (SWCNTs) that involves both solubilizing ionic liquids and electroactive moieties is reported. Our strategy is a simple and efficient methodology based on the stepwise functionalization of the nanotube surface with two different organic moieties. In a first instance, oxidized SWCNTs are amidated with ionic liquid precursors, and further treated with n‐butyl bromide to afford SWCNTs functionalized with 1‐butylimidazolium bromide. This approach allows tuneable polarity induced by anion exchange, which has an effect on the relative solubility of the modified SWCNTs in water. Subsequently, a 1, 3‐dipolar cycloaddition reaction was performed to introduce the electron‐acceptor 11, 11, 12, 12‐tetracyano‐9, 10‐anthra‐para‐quinodimethane (TCAQ) unit on the SWCNTs. Furthermore, to evaluate the influence of the functional group position, the TCAQ electroactive molecule was anchored through an esterification reaction onto previously oxidized SWCNTs, followed by the Tour reaction to introduce the ionic liquid functions. IR and Raman spectroscopies, thermogravimetric analysis (TGA), UV/Vis/NIR spectroscopy, transmission electron microscopy (TEM), and X‐ray photoelectron spectroscopy (XPS) were employed and clearly confirmed the double‐covalent functionalization of the SWCNTs.